Recurrent rearrangements of human amylase genes create multiple independent CNV series - Shwan, Nzar A.A.; Louzada, Sandra; Yang, Fengtang; Armour, John A.L. (Wiley, 2017)
The human amylase gene cluster includes the human salivary (AMY1) and pancreatic amylase genes (AMY2A and AMY2B), and is a highly variable and dynamic region of the genome. Copy number variation (CNV) of AMY1 has been implicated in human dietary adaptation, and in population association with obesity, but neither of these findings has been independently replicated. Despite these functional implications, the structural genomic basis of CNV has only been defined in detail very recently. In this work, we use high-resolution analysis of copy number, and analysis of segregation in trios, to define new, independent allelic series of amylase CNVs in sub-Saharan Africans, including a series of higher-order expansions of a unit consisting of one copy each of AMY1, AMY2A, and AMY2B. We use fiber-FISH (fluorescence in situ hybridization) to define unexpected complexity in the accompanying rearrangements. These findings demonstrate recurrent involvement of the amylase gene region in genomic instability, involving at least five independent rearrangements of the pancreatic amylase genes (AMY2A and AMY2B). Structural features shared by fundamentally distinct lineages strongly suggest that the common ancestral state for the human amylase cluster contained more than one, and probably three, copies of AMY1.